2005
DOI: 10.1007/s10815-005-5998-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in serum LH and FSH levels using depot or daily GnRH agonists in controlled ovarian stimulation: influence on ovarian response and outcome of ART

Abstract: Patients with profound endogenous LH suppression by depot GnRH agonists show higher FSH stimulation dose requirements and lower oocyte number and fertilization rate, indicating a need for minimal LH activity in folliculogenesis and oocyte development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
(49 reference statements)
2
4
0
1
Order By: Relevance
“…Similar results have been reported elsewhere [16][17][18]. Sonntag et al report that long-term use of GnRH-a can lead to low levels of endogenous LH [19], thus it is important to supplement exogenous LH in patients with low LH levels [20]. Previous studies also found that patients with low serum LH levels achieved better clinical pregnancy rates after adding exogenous LH [15,[21][22][23][24].…”
Section: Discussionsupporting
confidence: 80%
“…Similar results have been reported elsewhere [16][17][18]. Sonntag et al report that long-term use of GnRH-a can lead to low levels of endogenous LH [19], thus it is important to supplement exogenous LH in patients with low LH levels [20]. Previous studies also found that patients with low serum LH levels achieved better clinical pregnancy rates after adding exogenous LH [15,[21][22][23][24].…”
Section: Discussionsupporting
confidence: 80%
“… 82 The degree of pituitary suppression depends also on the GnRH-a formulation as well as the mode and dose of administration. 83 , 84 …”
Section: “Iatrogenic” Severe Lh and Fsh Deficiency During Assisted Rementioning
confidence: 99%
“… 84 , 85 Some authors attributed this phenomenon to the profound suppression of LH level after long downregulation GnRH-a protocol. 83 , 84 Several studies have been conducted with the aim of establishing a valuable cutoff of circulating LH level after pituitary desensitization in order to identify those patients, but the results obtained are conflicting. 84 , 85 Conversely, a meta-analysis published by Kolibianakis et al 86 showed no evidence that low endogenous LH levels, which may occur during long protocols of ovarian stimulation for in vitro fertilization, require exogenous LH supplementation to improve the probability of ongoing pregnancy.…”
Section: “Iatrogenic” Severe Lh and Fsh Deficiency During Assisted Rementioning
confidence: 99%
“…Prominent protocols for PCOS include the gonadotropin-releasing hormone agonist (GnRHa) long protocol and the GnRH antagonist protocol [12]. Two types of GnRHa pattern can be used to prevent premature luteinization: a low (0.1 mg) daily dose of GnRHa or a separate, higher dose (3.75 mg) of long-acting GnRHa analogue, which is also called depot GnRHa [17][18][19]. The depot GnRH agonist protocol is preferred for its convenient single-injection delivery and satisfactory pregnancy rates [20,21].…”
Section: Introductionmentioning
confidence: 99%